Avaliação do risco de contaminação do lençol freático, pelo herbicida tebuthiuron em cultura de cana-de-açúcar, utilizando geoestatística e simulador CMLS. - NICOLELLA, G. (1999)
Abstract: Nowadays, sugar cane production demands application of several herbicides of which, tebuthiuron, has been largely used. In an area intensivelycropped with sugar cane and susceptible to leaching due to edaphic conditions, CMLS (ChemicalMovement in Layered Soils) model was